What plant genetic resources for food and agriculture are available under the Plant Treaty and where is this information? - Gullotta, Gaia; Engels, Johannes M.M.; Halewood, Michael (MDPI, 2023)
Plant genetic resources for food and agriculture (PGRFA) are the building blocks upon which global food and nutrition security depend and are key to plant breeding for more resistant crops, but how available are they? To understand what PGRFA are available under the mechanisms created by the International Plant Treaty’s access and benefit-sharing, we conducted a comparative analysis of the five largest sources of pooled global data concerning PGRFA, including data conserved by and available to users under the Plant Treaty’s access and benefit-sharing (ABS) mechanism. These data sources were the registry of notification letters maintained by the Plant Treaty Secretariat and four international PGRFA databases: Genesys, European Search Catalogue for Plant Genetic Resources (EURISCO), World Information and Early Warning System on Plant Genetic Resources for Food and Agriculture (WIEWS) and Global Information System on PGRFA (GLIS). Our analysis revealed that a comprehensive and consistent overview of the PGRFA available under the Plant Treaty’s ABS conditions is not available. The GLIS is the most logical longer-term candidate to promote the provision of up-to-date and comprehensive snapshots of what PGRFA the Plant Treaty framework make available, primarily because it provides a mechanism (digital objective identifiers) to link together information from a range of information sources, including Genesys, WIEWS and EUEISCO and other online publications, and data sets concerning PGRFA in the multilateral system. Successful adoption of the GLIS could be promoted by creating novel incentives endorsed by the Governing Body to encourage Contracting Parties, Article 15 organizations, and individuals to share information about the materials they are making available under the Plant Treaty, in addition to the capacity-building for some GLIS users that is also necessary. These incentives could be included among the package of measures currently being considered by the Plant Treaty’s Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-Sharing.